Perbedaan Pengaruh Pemberian Kitosan Berat Molekul Tinggi dan Rendah terhadap Jumlah Pembuluh Darah pada Proses Penyembuhan Luka Pencabutan Gigi - Bella Sagita Puspita; Sularsih; Dian W. Damaiyanti (Denta Journal Kedokteran Gigi, 2015)
Background: Molecular weight is one of the chitosan characteristic that affects the effectiveness of application for wound healing in dental extraction. Chitosan could improve wound healing process because of its anti inflammation component and accelerateproliferation phase. Angiogenesis is one of the main component in proliferation phase because it can preserve cells function to accelerate wound healing process. Purpose: the aim of this experiment is to account blood vessels in wound healing of dental extraction using chitosan with different molecular weight. Materials and Methods: Thirty six male Rattus Norvegicus were divided into 3 groups. Group I (without chitosan), group II was given low molecular weight chitosan, group III was given high molecular weight chitosan. Rats were sacrificed on day 7 and on day 14 post extraction then they were examined by hystometri to see the change in blood vessels number. Result: Data were statistically analyzed with One Way ANOVA and LSD with degree of significant p<0,05 showed significant difference between high molecular weight chitosan group and low molecular weight chitosan group after 7 and 14 days observation. Conclusion: High molecular weight chitosan was found more effective to increase blood vessels amount at 7th day and decrease blood vessels amount that 14 day in wound healing of dental extraction process.